2016
DOI: 10.1039/c6ra00168h
|View full text |Cite
|
Sign up to set email alerts
|

Cubic and tetragonal ferrite crystal structures for copper ion immobilization in an iron-rich ceramic matrix

Abstract: This study proposes a “waste-to-resource” strategy by reusing the incineration ash of municipal wastewater sludge as a ceramic material to immobilize copper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…XRD patterns was obtained to specify the crystal structure of the prepared CuFe 2 O 4 nanoparticles. As shown in Figure a, the strong and sharp reflection peaks in XRD patterns of nanoparticles are corresponded to the cubic phase of CuFe 2 O 4 with a good crystallinity (JCPDS file No:04–005‐7637) . According to the EDX analysis, the distribution of the elements in the produced CuFe 2 O 4 nanoparticles was Cu = 15.66%, Fe = 32.17% and O = 50.98%, that the its corresponding iron\copper ratio 2.05 is almost agreement to the atomic ratio in the formula CuFe 2 O 4 (Figure b).…”
Section: Resultsmentioning
confidence: 71%
“…XRD patterns was obtained to specify the crystal structure of the prepared CuFe 2 O 4 nanoparticles. As shown in Figure a, the strong and sharp reflection peaks in XRD patterns of nanoparticles are corresponded to the cubic phase of CuFe 2 O 4 with a good crystallinity (JCPDS file No:04–005‐7637) . According to the EDX analysis, the distribution of the elements in the produced CuFe 2 O 4 nanoparticles was Cu = 15.66%, Fe = 32.17% and O = 50.98%, that the its corresponding iron\copper ratio 2.05 is almost agreement to the atomic ratio in the formula CuFe 2 O 4 (Figure b).…”
Section: Resultsmentioning
confidence: 71%
“…Reactions between copper and iron ions have also been reported previously in a solid CuO-Fe 2 O 3 system followed by the formation of CuFe 2 O 4 with a spinel structure. 37 The copper leachability from the spinel was found to decrease by over two orders in magnitude in comparison with that from copper oxides in acetic acid solutions, 37 which conrmed the effective immobilization of copper ions in copper-adsorbed y ash aer sintering. With a further increase in the sintering temperature, the CuFe 2 O 4 peaks eventually grew while the CuO signals reduced accordingly.…”
Section: Leaching Experimentsmentioning
confidence: 99%
“…Previous studies have also reported a lower sintering temperature for a ferrite spinel when compared to that of an aluminate spinel. 36,37 The tendency for peaks to shi with an increase in temperature was further analyzed and the results are shown in Fig. 4c.…”
Section: Incorporation Mechanisms Of Copper In Aluminum-and Iron-richmentioning
confidence: 99%
See 2 more Smart Citations